Ion channels and electrical excitability in native murine anterior pituitary corticotrophs - Liang, Zhi (The University of Edinburgh, 2013)
As a central component of the hypothalamic-pituitary-adrenal (HPA) axis, the anterior pituitary corticotrophs play an important role in the regulation of HPA axis function and the neuroendocrine response to stress. Pituitary corticotrophs integrate stress-induced stimulatory signals (CRH and AVP) from the brain together with the negative feedback control from circulating glucocorticoid hormones to coordinate adrenocorticotrophin hormone (ACTH) secretion. Previous studies have classified pituitary corticotrophs as both endocrine and electrically excitable cells with a number of ion channels and signaling pathways implicated in the control of their electrical properties and ACTH secretion. However, the mechanisms involved in native corticotrophs are poorly understood partly due to the current limitations of identifying physiological intact corticotrophs. To address the electrophysiological properties of native murine corticotrophs, a lentiviral transduction system was developed, using a minimal pro-opiomelanocortin (POMC) promoter to drive the expression of enhanced yellow fluorescent protein (eYFP), to allow highly efficient and specific labeling and identification of corticotrophs in vitro. This approach, with patch clamp electrophysiological investigations, revealed metabolically intact native murine corticotrophs displayed spontaneous action potentials with highly heterogeneous firing patterns including single spikes and variable “pseudo plateau bursting” action potentials. The resting membrane potential of native murine corticotrophs was maintained by a TTXresistant background sodium conductance. Physiological concentrations of CRH/AVP rapidly depolarized native murine corticotrophs resulting in a sustained increase in the frequency of action potentials. Native murine corticotrophs express multiple outward potassium conductances with two major components mediated by intermediate-conductance calcium-activated (SK4) potassium channels and A-type potassium channels. Inhibition of SK4 channels with TRAM-34 lead to an increase in corticotroph excitability with firing pattern transition from single spikes to “pseudo plateau bursting”. When A-type potassium channels were blocked, the afterhyperpolarization amplitude of single spikes was decreased in some corticotrophs. In native murine corticotrophs, outward potassium current carried by large conductance calcium- and voltage- activated potassium (BK) channels was very low, which is in contrast with that in the mouse pituitary adenoma cell line (AtT20 cell line). Corticotroph cells from wild type (WT) mice and mice with a genetic deletion of the BK channel (BK-/-) were compared. The only potassium current that showed significant difference between WT and BK-/- corticotrophs was carried via the barium-sensitive inwardly rectifying (Kir) potassium channel. However, the blockage of Kir channels displayed no clear effect on corticotroph cell electrical excitability. Similar heterogeneous spontaneous firing patterns were found in WT and BK-/- corticotrophs. Taken together, the lentiviral-mediated expression of eYFP, driven by a minimal POMC promoter, provides an efficient method to identify physiological intact native murine anterior pituitary corticotrophs. These findings demonstrate that native murine anterior pituitary corticotrophs are spontaneous excitable cells that display significant heterogeneity of firing patterns. Results also reveal an important role of a background TTX-insensitive sodium conductance in controlling spontaneous and CRH/AVP evoked action potentials. Furthermore, an unexpected role for SK4 calcium-activated potassium channels in corticotroph excitability was revealed. In all, these studies give new insight into the physiology of corticotroph excitability and ACTH secretion, and provide the basis for understanding the roles of these ion channels in HPA axis function.
Keywords: ion channels; electrical excitability; native murine corticotrophs